2020
DOI: 10.1016/j.joca.2020.02.205
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously expressed CXC chemokine receptor type 7 is involved in inflammation of chondrocyte from mice

Abstract: 5W, 9W in each group in a random sample of3, application of chloral hydrate intraperitoneal injection anesthesia death, cardiac lavage after removing the damaged spinal cord tissue, immunohistochemical determination of GAP-43. Results: The first, to model after 1D,1W,2W,3W,5W,9W. BBB score, molding 1D after each score is 0points,1W groups of rat hindlimb has recovered, but the score is low, the group had no difference (P>0.05);2W B group, C group, D group was higher than that of A group were significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For the six marker genes previously identified, we found that CDKN1A, FOSB, STMN2, and SLC2A3 genes were reported to be associated with cartilage inflammation in OA (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). For example, the expression level of CDKN1A will increase correspondingly during cartilage degeneration (44), IL-17 and IL-1beta induced collagenase-3 production through AP-1 occurred with differential protein complex, and stimulation resulted in FOSB activation (52), STMN2 has significant differences between preserved and subchondral bone (48).…”
Section: Discussionmentioning
confidence: 85%
“…For the six marker genes previously identified, we found that CDKN1A, FOSB, STMN2, and SLC2A3 genes were reported to be associated with cartilage inflammation in OA (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). For example, the expression level of CDKN1A will increase correspondingly during cartilage degeneration (44), IL-17 and IL-1beta induced collagenase-3 production through AP-1 occurred with differential protein complex, and stimulation resulted in FOSB activation (52), STMN2 has significant differences between preserved and subchondral bone (48).…”
Section: Discussionmentioning
confidence: 85%